Heat Transfer and Entropy Generation in Concentric/Eccentric Double-Pipe Helical Heat Exchangers - Kurnia, J.C. (Taylor and Francis Ltd., 2020)
Double-pipe helical heat exchangers are integral to contemporary mechanical refrigeration equipment. Modification of flow geometry has been widely adopted to enhance heat transfer performance of a heat exchanger. The objective of this study is to numerically investigate heat transfer and entropy generation in a double pipe helical heat exchanger with various cross-sections. A computational model for laminar convective heat transfer was developed and validated against the results from previously published literature. To capture entropy generation, the entropy balance equation for open system is adopted. Effect of inner pipe Dean number, inner pipe and annulus inlet mass flow rate ratio, eccentricity, and flow configuration (co-flow and counter-flow) were examined and discussed in light of computational results. To ensure fair comparison, the considered geometries have same inner pipe cross-section area, same annulus cross-section area, and same outer surface area of inner pipe. The results suggest that square cross-section offers best performance in term of heat transfer, pressure drop and entropy generation. In addition, concentric configuration is more appropriate for low flow rate application while eccentric outer configuration is more suitable for high flow rate application. Â© 2019, Â© 2019 Taylor & Francis Group, LLC.